2017
DOI: 10.1038/s41598-017-03696-8
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in prostaglandin biosynthesis in neutrophils during acute inflammation

Abstract: The severity and course of inflammatory processes differ between women and men, but the biochemical mechanisms underlying these sex differences are elusive. Prostaglandins (PG) and leukotrienes (LT) are lipid mediators linked to inflammation. We demonstrated superior LT biosynthesis in human neutrophils and monocytes, and in mouse macrophages from females, and we confirmed these sex differences in vivo where female mice produced more LTs during zymosan-induced peritonitis versus males. Here, we report sex diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 38 publications
1
55
0
Order By: Relevance
“…Very recently, it was discovered that microglial response to environmental challenges is sex-specific [ 57 ]. There are also differences between male and female in the quantity and function of neutrophils and monocytes [ 58 61 ]. Further, inflammatory responses and injury outcome after neonatal HI have been reported to diverge according to gender, with enhanced inflammation, microglia activation and monocyte infiltration in males compared to females [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, it was discovered that microglial response to environmental challenges is sex-specific [ 57 ]. There are also differences between male and female in the quantity and function of neutrophils and monocytes [ 58 61 ]. Further, inflammatory responses and injury outcome after neonatal HI have been reported to diverge according to gender, with enhanced inflammation, microglia activation and monocyte infiltration in males compared to females [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are too few data for molecular mechanisms consideration, but an interconnection is promising. The sex difference in the basal levels of PGE 2 and 6-keto-PGF 1α , and the prostaglandins release under LPS stimulation were shown for human neutrophils [ 2 ]. It is noteworthy that male neutrophils have initially higher levels of both PGs, and this difference remains after LPS stimulation [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sex difference in the basal levels of PGE 2 and 6-keto-PGF 1α , and the prostaglandins release under LPS stimulation were shown for human neutrophils [ 2 ]. It is noteworthy that male neutrophils have initially higher levels of both PGs, and this difference remains after LPS stimulation [ 2 ]. The molecular mechanisms and biological significance for this discrepancy remains a matter of future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has earlier been noticed that the severity and course of inflammatory process differ between women and men. Simona Pace and colleagues (Pace et al, 2017) found that freshly isolated and immediately LPS stimulated human neutrophils from males produced more PGE2 than cells from females and that this might be caused by increased COX-2 expression and by shunting phenomena due to suppressed leukotrienes formation. They conclude that the observed sex-difference might help to explain, at least in part, the sex dimorphism in innate immune disorders such as sepsis and post-surgery infections.…”
Section: Linking Covid-19 Clinical Observations and Pge2mentioning
confidence: 99%